2022
DOI: 10.2147/ccid.s370741
|View full text |Cite
|
Sign up to set email alerts
|

Hypopigmented Mycosis Fungoides: A Clinicopathological Review of 32 Patients

Abstract: Background: Hypopigmented mycosis fungoides (hMF) is gradually acknowledged by more dermatologists, yet a consensus regarding its characteristics is not reached. The profile of Chinese hMF patients has not been deeply reviewed previously. Our research may contribute to the understanding of hMF, especially the Chinese patients with Fitzpatrick phototypes of III and IV. Aim: To have a better understanding of hMF in terms of clinical, histopathological and immunohistochemical features in the Chinese population an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
1
2
1
Order By: Relevance
“…The current study confirmed that hMF affected mainly younger patients, with a median age at onset of 8.5 years and a median age at definitive diagnosis of 11 years. This was also corroborated by previous groups ( 5 , 13 15 , 19 ). Different groups have reported different intervals between disease onset and diagnosis ( 4 , 9 , 15 17 , 19 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The current study confirmed that hMF affected mainly younger patients, with a median age at onset of 8.5 years and a median age at definitive diagnosis of 11 years. This was also corroborated by previous groups ( 5 , 13 15 , 19 ). Different groups have reported different intervals between disease onset and diagnosis ( 4 , 9 , 15 17 , 19 ).…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the interval from disease onset to diagnosis ranged from 2 months to 16 years, with a median of 24 months. In comparison with previous reports (4,9,13,14,(16)(17)(18)(19)(20), patients treated for hMF at our cutaneous lymphoma centre were younger and had improved diagnosis and treatment outcomes.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations